Map out the legitimacy of source, story actors, and types of frames on the choice of development issues in faith media - Negesse Belay Gessese (Cogent Arts & Humanities)
The purpose of this study is to investigate the impact of sources, actors, and frames on development issues in Ethiopia’s faith media. The quantitative method compares the contents of two Ethiopian religious magazines to this end (Hamer and Hintset). SPSS software was used for data analysis, and both descriptive and inferential statistical techniques were used for data presentation. The findings revealed that social development stories were the most frequently found in both magazines. Furthermore, binary logistic regression analysis revealed that story actors and frame types influenced the selection of economic, historical, and moral development stories. The selection of cultural development stories in Hamer magazine, on the other hand, was influenced solely by frame types. The choice of economic, historical, and moral development frames in Hintset magazine was influenced by frame types. Peace development stories in both magazines were influenced by story actors and frame types, and frame types influenced the choice of social development stories in both magazines (Wald = 86, df = 10, p = .000) and (Wald = 57.6, df = 10, p = .000) in Hamer and Hintset magazines consecutively. Finally, the sources, story actors, and frame types of both magazines had no influence on natural resource and political development stories.